Czech Magic : Implementing Inflation-Forecast Targeting at the CNB - Clinton, Kevin (IMF Working Papers; Working Paper ;, 2017)
This paper describes the CNB's experience implementing an inflation-forecast targeting (IFT) regime, and the building of a system for providing the economic information that policymakers need to implement IFT. The CNB's experience has been very successful in establishing confidence in monetary policy in the Czech Republic and should provide useful guidance for other central banks that are considering adopting an IFT regime.